2021
DOI: 10.3390/polym13071056
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Plasma Treated-Electrospun Polyhydroxyalkanoate Scaffolds for Hydrophilicity Improvement and Cell Adhesion

Abstract: Poly(hydroxyalkanoates) (PHAs) with differing material properties, namely, the homopolymer poly(3-hydroxybutyrate), P(3HB), the copolymer poly(3-hydroxybutyrate-co-3-hydroxyvalerate), P(3HB-co-3HV), with a 3HV content of 25 wt.% and a medium chain length PHA, and mcl-PHA, mainly composed of 3-hydroxydecanoate, were studied as scaffolding material for cell culture. P(3HB) and P(3HB-co-3HV) were individually spun into fibers, as well as blends of the mcl-PHA with each of the scl-PHAs. An overall biopolymer conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Samples PLA_DC and PLA_DC_EDAC exhibited the highest cytocompatibility. This result was expected as the plasma treatment increased the hydrophilic character of PLA and the wettability of the surface affects cell behavior, especially the cell attachment [37][38][39][40][41]. However, without further immobilization of chlorhexidine, these samples did not exhibit any antibacterial effect.…”
Section: Cytocompatibility Resultsmentioning
confidence: 85%
“…Samples PLA_DC and PLA_DC_EDAC exhibited the highest cytocompatibility. This result was expected as the plasma treatment increased the hydrophilic character of PLA and the wettability of the surface affects cell behavior, especially the cell attachment [37][38][39][40][41]. However, without further immobilization of chlorhexidine, these samples did not exhibit any antibacterial effect.…”
Section: Cytocompatibility Resultsmentioning
confidence: 85%
“…These reports have further broadened current and perspective applications of PHAbased materials (Table 1). SEM studies demonstrated significant variability on the nanolevel 3D structures of the ES mixtures P(3HB): mcl-PHA [62] and foams PLLA/PHA [63]. SEM studies demonstrated significant variability on the nanolevel 3D structures of the ES mixtures P(3HB): mcl-PHA [62] and foams PLLA/PHA [63].…”
Section: Discussionmentioning
confidence: 93%
“…These reports have further broadened current and perspective applications of PHAbased materials (Table 1). SEM studies demonstrated significant variability on the nanolevel 3D structures of the ES mixtures P(3HB): mcl-PHA [62] and foams PLLA/PHA [63]. Studies have proven that combining different types of PHAs (see Figure 4) in right proportions with other material significantly enhances wide variety of their properties [60].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, it is essential to adhere the copper to the surface of the filter firmly because if the copper detaches from the filter, a human can inhale the copper, which becomes a toxin when inside the body [6]. In previous works, modifications to the surface of a filter using an ion beam enabled the strong adherence of materials onto the filter [15][16][17][18]. The adhesion was accomplished without damaging the fibers of the filter.…”
Section: Introductionmentioning
confidence: 99%